SENSITIVITY OF CRU AND ERA5 PRECIPITATION DATASETS TO ENSO FORCINGS FOR INDONESIAN CLIMATE DURING 1970-2024 - Prastowo, Tjipto (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
Observational precipitation datasets for countries around the globe as part of climate parameters are available in time-series acquired from ground-based and satellite-based monitoring stations. This study reports two datasets for rainfall variability in Indonesia during 1970–2024 provided by Climatic Research Unit (CRU) University of East Anglia, UK for the ground-based data and ERA5, the fifth version of European Centre for Medium-Range Weather Forecasts (ECMWF) for the satellite-based measurements. The main aim of the study was to examine sensitivity of both datasets to climatic ENSO forcings, determining how strong El Niño and La Niña events influenced Indonesian rainfall variability. The methods in this study included accessing reliable sites for collecting and processing Indonesian precipitation datasets of different techniques and sea surface temperature data during observations. The results and corresponding discussions are summarised as follows. While El Niño and La Niña events indicate asymmetric behaviours, the ENSO forcings affect the precipitation datasets derived from two measurement techniques. Firstly, the datasets from CRU and ERA5 are coincident with years of extreme ENSO events. Secondly, despite the apparent difference in magnitude between observed rainfall intensities, the CRU and ERA5 datasets are found to be self-consistent in describing natural phenomena. Thirdly, with a higher resolution ERA5 datasets are more sensitive to the ENSO forcings than CRU datasets when applied to climatic conditions in Indonesia. ABSTRAK Data observasi presipitasi sebagai bagian dari parameter iklim untuk wilayah teritorial se dunia dapat diperoleh dari stasiun monitor di darat dan di udara. Studi ini melaporkan dua jenis data presipitasi di Indonesia antara 1970–2024 yang disediakan oleh Climatic Research Unit (CRU), University of East Anglia, UK untuk stasiun monitor di darat dan ERA5, generasi kelima dari European Centre for Medium-Range Weather Forecasts (ECMWF) untuk pengukuran satelit. Tujuan penelitian ini adalah membandingkan sensitivitas kedua jenis data presipitasi terhadap pengaruh ENSO dengan cara menentukan seberapa kuat El Niño dan La Niña memengaruhi variabilitas intensitas curah hujan di Indonesia. Metode yang digunakan dalam penelitian ini adalah mengakses laman yang kredibel untuk pengumpulan dan pemrosesan data presipitasi di Indonesia dan temperatur muka laut selama observasi berlangsung. Hasil-hasil penelitian dan pembahasan terkait adalah sebagai berikut. El Niño and La Niña menunjukkan sifat asimetrik, dimana kedua fenomena alam tersebut berpengaruh terhadap data presipitasi di Indonesia yang diperoleh dari dua teknik pengukuran. Pertama, data presipitasi CRU dan ERA5 sesuai dengan tahun-tahun kejadian ENSO ekstrem. Kedua, meskipun terdapat perbedaan signifikan antara intensitas curah hujan yang dilaporkan oleh CRU dan ERA5, data presipitasi CRU dan ERA5 bersifat self-consistent dalam mendeskripsikan fenomena alam. Ketiga, dengan tingkat resolusi yang lebih tinggi data presipitasi ERA5 terbukti lebih sensitif terhadap pengaruh ENSO ekstrem daripada data presipitasi CRU untuk kondisi iklim di Indonesia.